Adoption of improved cassava varieties by processors is linked to processing characteristics and products biophysical attributes - Abass, A.; Awoyale, W.; Ogundapo, A.T.; Oluwasoga, O.; Nwaoliwe, G.; Oyelekan, J.; Olarinde, L. (Hindawi Limited, 2022)
Evidence from community cassava processors on product quality traits that influence variety adoption was combined with laboratory methods to identify potential predictors of quality traits of new varieties. The study revealed that high product yield, high starch content, high solubility index (SI), high peak viscosity (PV), low setback viscosity, and delayed root color change (delayed postharvest physiological deterioration) are possible laboratory indicators that could be used as proxies for predicting product quality and variety adoption decisions of cassava processors. Fufu exhibited higher swelling power, SI, and PV than gari from the same varieties. Processors preferred quality characteristics are difficult to measure for several hundreds of new germplasms in the early stages of the breeding cycle. The information presented may be helpful during the breeding of new, improved varieties by using the physical and chemical properties of the roots that predict processors’ preferred quality traits.